Local Wisdoms in Bengkulu Play Script “Sayembara Putri Gading Cempaka” by Agus Setiyanto - Dedi Febriyanto; Mulyanto Widodo (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2021)
The purpose of this research is to describe the local wisdom in the Bengkulu play script "Sayembara Putri Gading Cempaka" by Agus Setiyanto. This study used a descriptive qualitative method with a sociological approach. The data of this research are words, sentences, and discourses in the local wisdom of the Bengkulu play script Sayembara Putri Gading Cempaka written by Agus Setiyanto. The data were collected by the read-note technique. The data collection and analysis were conducted simultaneously so that the data could be triangularly validated with the data source. The data analysis was done by the content analysis technique method. The results showed that Agus Setiyanto's Bengkulu play Sayembara Putri Gading Cempaka had various local wisdoms. The local wisdom covered tangible local wisdom; (1) taboos and obligations of a leader, (2) traditions, (3) values, (4) advice, (5) way of life, and (6) local languages.